2021
DOI: 10.1111/bph.15377
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine palmitoyltransferase 1C negatively regulates the endocannabinoid hydrolase ABHD6 in mice, depending on nutritional status

Abstract: Background and Purpose: The enzyme α/β-hydrolase domain containing 6 (ABHD6), a new member of the endocannabinoid system, is a promising therapeutic target against neuronal-related diseases. However, how ABHD6 activity is regulated is not known. ABHD6 coexists in protein complexes with the brain-specific carnitine palmitoyltransferase 1C (CPT1C). CPT1C is involved in neuro-metabolic functions, depending on brain malonyl-CoA levels. Our aim was to study CPT1C-ABHD6 interaction and determine whether CPT1C is a k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…Therefore, through endocannabinoid signaling, ABHD6 in VMH plays a key role in regulating whole-body energy balance. So far, our group has demonstrated that ABHD6 hydrolase activity is specifically regulated by nutritional status in the hypothalamus and is activated on fasting as compared to the fed state [ 160 ]. In that study, we also identified carnitine palmitoyl-transferase 1C (CPT1C), an energy sensor in the hypothalamus [ 161 , 162 ], as the first negative regulator of ABHD6 activity [ 160 ].…”
Section: Hypothalamic Endocannabinoid Signaling In Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, through endocannabinoid signaling, ABHD6 in VMH plays a key role in regulating whole-body energy balance. So far, our group has demonstrated that ABHD6 hydrolase activity is specifically regulated by nutritional status in the hypothalamus and is activated on fasting as compared to the fed state [ 160 ]. In that study, we also identified carnitine palmitoyl-transferase 1C (CPT1C), an energy sensor in the hypothalamus [ 161 , 162 ], as the first negative regulator of ABHD6 activity [ 160 ].…”
Section: Hypothalamic Endocannabinoid Signaling In Obesitymentioning
confidence: 99%
“…So far, our group has demonstrated that ABHD6 hydrolase activity is specifically regulated by nutritional status in the hypothalamus and is activated on fasting as compared to the fed state [ 160 ]. In that study, we also identified carnitine palmitoyl-transferase 1C (CPT1C), an energy sensor in the hypothalamus [ 161 , 162 ], as the first negative regulator of ABHD6 activity [ 160 ]. However, the role of CPT1C regulation of ABHD6 activity in whole-body energy metabolism needs further investigation.…”
Section: Hypothalamic Endocannabinoid Signaling In Obesitymentioning
confidence: 99%
“…Carnitine palmitoyl transferase 1c (CPT1c) is a member of the carnitine palmitoyl transferase 1 family (which includes CPT1a and CPT1b), participating in the regulation of physiological functions such as energy metabolism and feeding ( Obici et al, 2003 ). Proteomic studies have revealed that CPT1c and ABHD6 may interact ( Brechet et al, 2017 ; Schwenk et al, 2019 ), and Miralpeix et al confirmed this through coimmunoprecipitation (co-IP) and fluorescence resonance energy transfer (FRET) analyses ( Miralpeix et al, 2021 ). Furthermore, the content of eCB in CPT1c-knockout (KO) mice is decreased ( Lee and Wolfgang, 2012 ), indicating that interaction between CPT1c and ABHD6 may be involved in eCB hydrolysis.…”
Section: Molecular Mechanism Of Abhd6-specific Signalingmentioning
confidence: 99%
“…Further studies have confirmed that CPT1c has a significant effect on the enzymatic activity of ABHD6. Upon CPT1c overexpression, ABHD6 enzyme activity is decreased by approximately 60%, whereas activity increases significantly in CPT1c-KO mice ( Miralpeix et al, 2021 ). Protein interaction between CPT1c and ABHD6 depends on malonyl-CoA ( Figure 2 ).…”
Section: Molecular Mechanism Of Abhd6-specific Signalingmentioning
confidence: 99%
See 1 more Smart Citation